THE INFLUENCE OF INTRINSIC MOTIVATION, EXTRINSIC MOTIVATION, AND COMPETENCE TOWARDS ACCOUNTING PRACTICE ON MICRO, SMALL, AND MEDIUM ENTERPRISES IN LOCAL REGENCY - Deseria Wijayanti; Agung Praptapa; Bambang Setyobudi Irianto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
Micro, Small and Medium Enterprises (MSMEs) is one of the economic activities conducted by most people in Indonesia. MSMEs have an important role in helping the development of the economy in Indonesia. However MSMEs is one of the important factors in economic development in Indonesia, but there are still many MSMEs perpetrators that have not applied accounting practice to their business. In fact, accounting information is very useful for MSMEs because it is a tool used by information users for decision making. This research aimed to analyze the influence of intrinsic motivation, extrinsic motivation, and competence towards accounting practice in Local Regency.This research used the 2 factors motivation theory and Goal Setting Theory. Motivation theory in this research will support the measurement of intrinsic motivation and extrinsic motivation MSMEs owners to do accounting practices in MSMEs. Meanwhile, goal setting theory is used as the base of assumption about the relationship between goals set and performance owner or managers of MSMEs.The population of this research was 34.455 business on the Department of Industry and Trade of MSMEs in Local Regency. The sample was 100 business unit MSMEs with trade, hotel, and restaurant sectors that calculated by Slovin formula. Stratified sampling technique is used in this research. Data collection in this study uses a questionnaire that is distributed directly to respondents.The results show that intrinsic motivation and competence variable has a positive affect on accounting practice in Local Regency. Extrinsic motivation has a negative effect on accounting practice in Local Regency.